Cutting procedures with improved visual effects and haptic interaction for surgical simulation systems. (February 2020) - Shi, Wen; Liu, Peter Xiaoping; Zheng, Minhua
Highlights: A new volumetric geometric model was proposed for cutting procedures in surgical simulation. The multidimensional parameters including gradient, density and second derivative are obtained by the pretreatment of gray value, which are introduced for improving the resolution between soft tissues on volume rendering. The meshless physical model is applied to express the biomechanical properties of soft tissues and the constant parameters are replaced with variables related to multidimensional parameters, which realizes the influence of different biological structures on feedback forces. The physical model and the geometric model are integrated and the haptic interaction is consistent with the presentation of visual effect. Compared with the conventional cutting model, both visual effect and haptic interaction are improved in the proposed volumetric geometric model. Abstract: Background and objectives: Surface rendering and physical models with constant parameters are often employed for cutting procedures in conventional surgical simulators. As a consequence, the internal structures of soft tissues cannot be rendered properly and haptic interaction is unrealistic. In order to improve both the visual and force feedback, a new volumetric geometric model is introduced. Methods: In this paper, we introduce a new volumetric geometric model, for which multidimensional parameters are derived from the gray values to map the color and transparency of the 3D soft tissues. In the meantime, the biomechanical properties of soft tissues are described by a meshless physical model and the model parameters are closely correlated to the multidimensional parameters of the developed volumetric geometric model. As a beneficial result, the force feedback changes according to the physical properties of different soft tissue structures, which reflects better the real-life scenarios during the course of cutting procedures. Results and Conclusions: Simulation results show that both the surface and internal structures of soft tissues can be rendered properly and the boundaries between different tissue structures are visually distinct in incision. The curves of feedback force change according to the different structures of soft tissue, improving haptic interaction. Compared with the conventional cutting model, both visual effect and haptic interaction are improved in the proposed volumetric geometric model.